Sulfonamide Resistance in Chicken Coccidiosis: A Clinico-Pathological Study (Bangladesh Journal of Microbiology, 2010)
Coccidiosis is a disease of great economic importance for the emerging poultry industry of Bangladesh. Sulfonamides have been used extensively for treatment and control of chicken coccidiosis. However, there have been complaints regarding failure of Esb3 ® (sodium sulfachloropyrazine monohydrate; Ciba-Geigy) in treating clinical coccidiosis. Therefore this study was undertaken to examine the degree of sulfonamide resistance of field coccidian isolates. Four groups of 12-day-old chicks were infected with 104 sporulated oocysts of four field coccidian isolates. Each group contains four subgroups containing 8 chicks in each subgroup, among which one subgroup remained as infected untreated control and another 3 subgroups were treated with 30% Esb3 ® @ 1 , 2, or 2.5 g/l of drinking water for 3 consecutive days. The sulfonamide resistance was assessed on the basis of faecal oocyst counts and clinico-pathological findings. There was no significant difference (p >0.05) in weight gain between untreated chicks and the chicks treated @ 1 and 2 g/l. However, a significantly higher (p